The economics of aid - Healey, J. M. (London : Routledge & K. Paul, 1971)
The main aspects of foreign aid to developing countries in terms of economic concepts and principles. The book gives an economic definition of aid and considers the motives for giving aid and the principles on which it may be allocated. He looks at the effect on the economic growth of developing countries of both the aid given and the need to repay the debt, and the effect on trade patterns and resource allocation of tying aid to one particular project, or one source of goods.
Bibliography: p. 105-107.
usc 18/05/18
Loans
Keywords: Economic assistance; Developing countries